Synthesis and characterization of zinc layered hydroxide cloprop nanocomposite and its controlled release property - Hashim Norhayati, Hussein Mohd Zobir, Md Isa Illyas, Kamari Azlan, Mohamed Azmi (Universiti Pendidikan Sultan Idris, 2014)
Synthesis and characterization of zinc layered hydroxide cloprop nanocomposite and its controlled release property by Hashim Norhayati, Hussein Mohd Zobir, Md Isa Illyas, Kamari Azlan, Mohamed Azmi,